2014
DOI: 10.1186/1748-717x-9-153
|View full text |Cite
|
Sign up to set email alerts
|

A treatment planning study comparing Elekta VMAT and fixed field IMRT using the varian treatment planning system eclipse

Abstract: BackgroundThe newest release of the Eclipse (Varian) treatment planning system (TPS) includes an optimizing engine for Elekta volumetric-modulated arc therapy (VMAT) planning. The purpose of this study was to evaluate this new algorithm and to compare it to intensity-modulated radiation therapy (IMRT) for various disease sites by creating single- and double-arc VMAT plans.MethodsA total of 162 plans were evaluated in this study, including 38 endometrial, 57 head and neck, 12 brain, 10 breast and 45 prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
2
20
0
2
Order By: Relevance
“…Furthermore, the dosimetric advantages of SIB over SB have been previously demonstrated (14, 15,22). Compared to the most widely used sequential electron boost, (23,24). In the present study, our dose distribution analysis showed more conformity and less dose spilling to the ipsilateral breast tissue outside the boost volume with the SIB technique compared to SB technique.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the dosimetric advantages of SIB over SB have been previously demonstrated (14, 15,22). Compared to the most widely used sequential electron boost, (23,24). In the present study, our dose distribution analysis showed more conformity and less dose spilling to the ipsilateral breast tissue outside the boost volume with the SIB technique compared to SB technique.…”
Section: Discussionsupporting
confidence: 70%
“…While details differ between these studies – due on the one hand to variations in the considered prostate PTV contours, and on the other hand to different planning approaches – it was generally found that VMAT treatment offers at least as good quality plans as IMRT treatment, sometimes even with better sparing of organs at risk. Depending on whether one or two arcs were chosen for VMAT treatment and whether constant or variable dose rate irradiation was allowed, plan quality measures and OAR DVH values sometimes favoured IMRT, sometimes VMAT treatment [ 16 - 24 ]; however, all studies observed a marked reduction in treatment time by VMAT treatment, and generally a drastic reduction in monitor units.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT, which has the advantage of integrating a multileaf collimator, rotational fan, cone beam delivery system, and robotic arm linear accelerator, delivers a high radiation dose to the target while minimizing the exposure of the organs at risk. Moreover, the arc-based approach for VMAT delivery is designed to further improve dose distribution through dynamic modulation of the gantry rotation speed, dose rate, and multileaf collimator shaping, thereby generating patterns of intensity modulation that deliver optimal treatment doses to the patient [12,13]. Modern radiotherapy techniques are associated with better survival rates than conventional radiation delivery for numerous cancer treatments [14,15].…”
Section: Introductionmentioning
confidence: 99%